EZ MindMap for student-centered learning - Ab. Aziz, Sidek; Ruslan, Siti Noor Zakiah; Che Abdullah, Che Azurahanim; Chen, Soo Kien (Centre for Global Open Access Learning, Immersive Technology & Quality Assurance, Universiti Sains Islam Malaysia, 2017)
EZ Mind Map is a great presentation method which involves diagram or chart to summarize information, ideas, tasks or a solid description of the purpose of explaining a concept or idea. Meaningful learning is more easily achieved through mind map approach when new concepts are more specifically linked to the concept of a more general concept that has long been understood. Mind map involves diagram or chart is drawn to summarize information, ideas, tasks or a solid description of the purpose of explaining a concept or idea. Mind maps are used to improve memory through the subconscious mind. The main objective of this project is to review the use of EZ Mind Maps to improve student achievement, especially for students at the Faculty of Science, Universiti Putra Malaysia which has been implemented comprehensively through qualitative and quantitative approaches. The project is to study the effectiveness of learning through student achievement and assess the level of acceptance and suitability of using mind maps in the process of teaching and lifelong learning.